Triple Active Antiretroviral Regimen Including Enfuvirtide Via the Biojector is Effective and Safe. (2007) - Loutfy, Mona; Kovacs, Colin
Abstract : For full HIV virological suppression, three fully active antiretroviral agents are required. New drug classes should be included to ensure that agents are fully active. The addition of enfuvirtide and efavirenz to the present patient's new antiretroviral regimen ensured that two fully active agents were in use in the setting of a moderate degree of nucleoside resistance and a high level of protease resistance, and where non-nucleoside reverse transcriptase inhibitors were still fully active. Both viral load and CD4 count responded favourably to this regimen. The patient received support from physicians and clinic staff in the introduction and use of enfuvirtide. To reduce injection site reactions, a needle-free injection system (Biojector) proved effective.